KULTUR KOLEKTIVISTIK DALAM ORGANISASI BIROKRASI (Studi pada Biro Humas Sekretariat Daerah Provinsi Jawa Tengah) - Koesmastuti, Rieka Hapsari (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractCollectivism bureaucratic organization shows that the relationship between the members oforganization are personal, and high respect between each other. Meanwhile, Max Weber’s Theory ofBureaucracy configure the formal and non personal relation. This research want to see the uniquenessof collectivism bureaucratic organization in Public Relations Bureau in Regional Secretariat of CentralJava Government. By using case study method, this research is executed by depth interview and directobservation. The result is, Javanese culture is really affect the individual behavior in organization,and apparently, this will help the organization in achieving their objectives and goals effectively. Thisbecause, the strong Javanese organizational culture contribute to the conducive situation which is animportant pre-requirement in achieving organizational goals